Collateral Damages of Military Operations in Nigeria - Maigari, Muhammad Abdullahi (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The paper has chronologically documented all incidences of collateral damage caused by military operations in Nigeria. From 2009 to 2025, military personnel, alongside other armed forces, were deployed to different parts of Nigeria as part of a strategy for internal security management. In the course of discharging their duty, the Nigerian forces missed their targets and their attacks hit defenceless civilians nineteen times. This research aims to identify the causal factors for collateral damage in internal security operations by the Nigerian military in Nigeria and to examine its implications. To explore redress options for the victims or their relatives. An explanatory research design is adopted to explain the episodic collateral damage that military operations cause, especially in Northern Nigeria. The findings revealed that a total of 19 episodes of collateral damage occurred in Nigeria and all in Northern Nigeria, because that is where the military has been battling with different non-state actors who took up arms against the government and those who have been kidnapping people for ransom, killing people, and stealing their livestock. Also, operational negligence was identified as one of the major causes of collateral damage in Nigeria because all of the fighter jets possessed by the Nigerian military have high definition cameras that can view images accurately regardless of the distance to the ground; hence, the operators are supposed to distinguish between armed & unarmed people on the ground. Another factor is operational recklessness because they are supposed to differentiate between settlements/villages of terrorists and non-targeted villages before launching an attack. Therefore, it is recommended that the Federal Government, which has all the armed forces in Nigeria under its control, should ensure that they are well-trained to protect civilians when carrying out air raids to avoid collateral damage at all costs. Members of the National Assembly should enact laws that specifically punish security operatives who, out of negligence or deliberately, kill defenceless civilians or non-targets of attacks during military operations.